Pengaruh Motivasi Intrinsik,Kompensasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan (Studi Pada PT. Berlian Jasa Terminal Indonesia) - Fitriyanti Marditia S; Nurhadi Nurhadi (FORBISWIRA FORUM BISNIS DAN KEWIRAUSAHAAN - SINTA 4, 2021)
This study aims to analyze the effect of intrinsic motivation, compensation and work environment simulta-neously and partially on employee performance. The sample used in this study were 95 respondents using clustersampling technique and using Multiple Linear Regression analysis technique. The result is that intrinsic motiva-tion, compensation and work environment variables simultaneously affect employee performance. Partial testing ofintrinsic motivation and compensation variables has a positive and significant effect on employee performance.While the partial test of the work environment variable has no significant positive effect on the performance ofemployees of PT. Berlian Jasa Terminal Indonesia.